2012
DOI: 10.1212/wnl.0b013e318248df2b
|View full text |Cite
|
Sign up to set email alerts
|

Adult cases of mitochondrial DNA depletion due to TK2 defect

Abstract: TK2 mutations can cause mitochondrial myopathy with a slow progression. Comparison of patients with similar mutations but different disease progression might address potential mechanisms of mtDNA maintenance modulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(57 citation statements)
references
References 28 publications
3
53
1
Order By: Relevance
“…This adult case of indolent myopathy expands the clinical spectrum of TK2-related diseases. Five recently published adult cases revealed that TK2-related MDS can have early onset and slow progression worsening in adulthood, 6 as in our case, or it can present in adulthood. 5 All patients showed muscle involvement, including bulbar, facial, and axial weakness, whereas respiratory insufficiency seemed confined to the early-onset cases.…”
Section: Tk2 Mutation Presenting As Indolent Myopathysupporting
confidence: 59%
See 1 more Smart Citation
“…This adult case of indolent myopathy expands the clinical spectrum of TK2-related diseases. Five recently published adult cases revealed that TK2-related MDS can have early onset and slow progression worsening in adulthood, 6 as in our case, or it can present in adulthood. 5 All patients showed muscle involvement, including bulbar, facial, and axial weakness, whereas respiratory insufficiency seemed confined to the early-onset cases.…”
Section: Tk2 Mutation Presenting As Indolent Myopathysupporting
confidence: 59%
“…[1][2][3] However, the progression of weakness may vary, 4 as shown by recently described adult patients with late-onset myopathy. 5,6 To date, only 5 adult patients with TK2-related MDS have been reported. Herein, we describe a man who had several unusual features.…”
Section: Tk2 Mutation Presenting As Indolent Myopathymentioning
confidence: 99%
“…Other, less common, presentations include spinal muscular atrophylike presentation [13] and chronic progressive external ophthalmoplegia with proximal muscle weakness [23]. Milder presentations have been reported and include late onset proximal muscle weakness [15], adult-onset progressive myopathy [22], and sensorineural hearing loss [21].…”
Section: Tk2-related Myopathic Mdsmentioning
confidence: 99%
“…mtDNA content is typically severely reduced in muscle tissue. Electron transport chain (ETC) activity assays in skeletal muscle typically show decreased activity of multiple complexes with complex I, I + III, and IV being the most affected [13][14][15][16][17][18][19][20][21][22][23].…”
Section: Tk2-related Myopathic Mdsmentioning
confidence: 99%
“…The presence of modifying factors could however be demonstrated in diseases due to mutations of the POLG or TK2 nuclear genes and of the mtDNA-encoded ND1, ND4 and ND6 genes causing Leber Hereditary Optic Neuropathy (LHON). They were proposed to underlie the absence of symptoms despite the presence of the mutations in LHON [4] or to significantly modify the presentation in the case of POLG or TK2 [5,6].…”
Section: The Extreme Phenotypic Diversity Of Mitochondrial Diseases Imentioning
confidence: 99%